OPTIMASI PENJADWALAN KOAS DENGAN METODE BRANCH AND PRICE - , PULUT SURYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
âKepaniteraan klinikâ program is an important part of the medical education system. âPaniteraan clinicâ program is a medical education period emphasizing on the application of previous theories obtained from pre-clinic period. This program is conducted in hospitals or in pointed health centers. Doctor candidates conducting this program are often called trainee. The trainee scheduling is a set of management for some trainees allocated to some units in a certain period which is not an easy job. This thesis proposes a trainee scheduling optimality system as an integer programming problems which then will be solved by using branch and price method. This problem consists of objective function that is to minimize violation constraint as a total penalty cost and constraints function which contains of capacity constraints, formation requirements constraints, non availability constraints and set-up constraints also including maximum limit for consecutive activities consecutive holidays. The test result showed that this application can give solution in the completion of trainee scheduling problem optimally, but the model and the system built are still unable to solve the real scheduling case among medical trainees. The solution could be obtained at 82,3% duration, 62,5% group number and 41,7% unit number from the real case with testing time less than 60 minutes. Key words : optimality, Scheduling, branch and price, integer prgramming